Predicting Dropout From Organized Football: A Prospective 4-Year Study Among Adolescent and Young Adult Football Players - Van Yperen, Nico W.; Jonker, Laura; Verbeek, Jan (Frontiers in Sports and Active Living, 2022)
Previous studies have shown that enjoyment is one of the key predictors of dropout from organized sport, including organized football. However, prospective studies, particularly studies focused on long-term dropout, are largely lacking. Drawing on the basic principles of interdependence theory, in the present prospective study among 1,762 adolescent and young adult football players (27.1% women, mean age 17.74 years, SD = 1.35), we tested the predictive value of sport enjoyment, perceived alternatives, and restraining forces on football players’ short-term (six months) and long-term (four years) dropout from organized football. As anticipated, the results of the logistic regression and follow-up analyses indicate that players’ enjoyment was the main predictor of (short-term and long-term) dropout. In addition, relative to remainers, dropouts perceived more alternatives in terms of other sports, had fewer family members involved in their football club, and were older at the time they started playing organized football. We conclude that particularly measures aimed at enhancing sport enjoyment may prevent players from dropping out from organized football in both the short and long term. In addition, dropout rates may be reduced by attracting and engaging youth at a very young age (from 6 years), and their siblings, parents, and other family members as well.